Ensaio de policultivo, com diferentes densidades de estocagem de tilápia do nilo Oreochromis niloticus (Linnaeus, 1766) e camarao marinho Litopenaeus vannamei (Boone, 1931), em água doce - Candido, Afonso Souza (2002)
The present work deals with the analysis of results from the mixed culture of Nile tilapia Oreochromis niloticus with the marine shrimp Litopenaeus vannamei. The study was carried out in the Centro de Tecnologia em Aquicultura (CTA) of the Universidade Federal do Ceará, Fortaleza, Ceará, Brasil, between August and December 2001. The aim of the present study was to investigate the growth of both species in mixed culture in fresh water using two different stocking rates of fish and shrimp. The experiments were carried out during 120 days, corresponding to three treatments with three replicates, conducted in 9 tanks of 1 m³ capacity each, following a complete randomization design. For the statistical analysis, it has been used a factorial scheme 4 x 3 x 3 (4 stock density for fish, 3 stocking density for shrimp and 3 replicates) at 5% significance level, coming to a total of 36 treatments. Each tank received 20 fingerlings of O. niloticus together with 4, 8 or 12 post-larvae of L. vannamei, consisting of treatments A, B and C, respectively. The density of Nile tilapia was 20, 10, 5 and 2 tilapias/tank in the first, second, third and forth cultivation phase, respectively. The fish were fed twice a day, with commercial food containing 45% of crude protein (CP) in the first 40 days. Between 40 and 80 days they were fed with pelletized ration containing 35% CP and after that, food pellets containing 32% CP. The feed rate decreased monthly from 10 to 4%, at the rate de 2% a month. The means in weight (in grams) and length (in millimeters) were estimated by casual sampling of 25% of fish and shrimp of each tank every 20 days. At the same time, water quality was evaluated by measuring temperature, pH and salinity in both, tanks and artesian well. The measurements were taken one day before the biometrical sampling. At the end of experiments, the animals were captured obtaining an average production of 450.32, 437.72 and 510.38 grams fish per tank and 53.08, 113.44 and 167.64 grams shrimp per tank for treatments A, B and C, respectively.